2017
DOI: 10.17352/ijvsr.000015
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater Snail Distribution Related to Physicochemical Parameters and Aquatic Macrophytes in Giza and Kafr El-Shiekh Governorates, Egypt

Abstract: A fi eld work was conducted to study the density of the freshwater snail in relation to the vegetation cover as well as the physical and chemical properties in different watercourses. Two sites were selected in Giza governorate while, three sites were selected at Kafr El-Shiekh governorate. Water temperature, conductivity, total hardness, and pH were measured in the selected sites as well as bisphenol A (BPA) levels. Snail sampling was carried out and all types of macrophytes found in each site were collected,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The increase in presence of B. pfeifferi and the increase in abundance of B. sudanica and Bu. globosus at sites with a high macrophyte cover observed in our study, indicate that food availability and the accessibility of aquatic weeds as a suitable surface on which egg masses of snails are deposited play an important role [21,62,75,76]. On the contrary, the decrease in abundance of Bu.…”
Section: Discussionmentioning
confidence: 57%
“…The increase in presence of B. pfeifferi and the increase in abundance of B. sudanica and Bu. globosus at sites with a high macrophyte cover observed in our study, indicate that food availability and the accessibility of aquatic weeds as a suitable surface on which egg masses of snails are deposited play an important role [21,62,75,76]. On the contrary, the decrease in abundance of Bu.…”
Section: Discussionmentioning
confidence: 57%
“…(2010) , Mohammed et al . (2016) , and El-deeb et al . (2017) , many factors affect the density and distribution of snail species.…”
Section: Discussionmentioning
confidence: 96%
“…(2015) revealed that the mean values of water temperature ranged from 23.5 – 25.7°C at seven sites in the four northern Egyptian governorates; Giza, Ismailia, Menoufia, and Gharbia. The highest occurrence of the snail Biomphalaria alexandrina was recorded at 28°C and 31°C in two northern Egyptian governorates; Giza and Kafr El Shiekh ( El-deeb et al ., 2017 ). Salawu & Odaibo (2014) reported the suitability of the water temperature range 21.7 – 29°C in all river bodies at Ogun state, Nigeria, for the survival of aquatic snail species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations